Facile synthesis of Pd nanostructures in hexagonal mesophases as a promising electrocatalyst for ethanol oxidation1. Issue 18 (14th May 2015) - Ghosh, Srabanti; Remita, Hynd; Kar, Prasenjit; Choudhury, Susobhan; Sardar, Samim; Beaunier, Patricia; Roy, Partha Sarathi; Bhattacharya, Swapan Kumar; Pal, Samir Kumar
<x xml:space="preserve">Abstract</x> Synthesis of self-assembled Pd nanostructures supported with reduced graphene oxide nanosheets as a promising electrocatalyst for the electrooxidation of ethanol.